The Reality of Using Distance Learning in Public and Private Schools from Principles’ and Supervisors’ Perspectives in Jordan - Alshudifat, Mohamad Ismail (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of the use of distance e-learning in public and private schools from the point of view of school principals and supervisors in the Northern Mazar District. It is made up of (72) school principals and educational supervisors in the Northern Mazar District in the second semester of the year 2019/2020. The study showed that the reality of using distance e-learning in public and private schools from the point of view of principals and supervisors was medium، with a percentage (60.20%) and the arithmetic mean of the tool as a whole was (3.01)، with a medium degree. The field of "knowledge of the concept of distance e-learning" came in the first rank with the highest arithmetic average، which amounted to (3.35) and a percentage (67%) and an average degree، and in the second rank came the field of (employment of distance-learning e-learning tools) with an arithmetic average of (3.20). With a percentage (64%) and a medium degree، followed by the field (obstacles of distance e-learning) in the third place، with an arithmetic average of (3.10) and a percentage (62%) and at a medium degree، and the field (awareness of the importance of distance education) achieved the last rank، with an arithmetic average (2.42)، with a percentage (48.4%) and a low degree. The results of the study also showed that there are no statistically significant differences at the significance level (α ≤ 0.05) between the average responses of the study sample towards the reality of using distance e-learning in schools due to the variable years of experience and qualification. While there were statistically significant differences (α ≤ 0.05) due to the gender variable in favor of females، the study recommended the necessity of increasing training programs on distance learning e-learning applications and software، and providing the educational field with educational brochures on distance education to spread e-learning awareness.